Solution‐Growth Strategy for Large‐Scale "CuGaO2 Nanoplate/ZnS Microsphere" Heterostructure Arrays with Enhanced UV Adsorption and Optoelectronic Properties. (18th April 2017) - Li, Yanmei; Song, Yun; Jiang, Yingchang; Hu, Mingxiang; Pan, Zhichang; Xu, Xiaojie; Chen, Hongyu; Li, Yuesheng; Hu, Linfeng; Fang, Xiaosheng
Abstract : Intrinsically p‐type conductivity and a wide bandgap of ≈3.6 V endow inorganic delafossite CuGaO2 with great promise for fabricating high‐performance UV photodetectors. Nevertheless, CuGaO2 ‐based optoelectronic devices hindered because the intrinsic direct transitions are symmetry forbidden in CuGaO2 . This study reports a large‐area synthesis of "CuGaO2 nanoplate/ZnS microsphere" heterostructure arrays using a facile solution‐based strategy associated with an oil/water interfacial self‐assembly approach. It is found that a large number of ZnS microspheres with a polycrystalline structure grow on the top surface of CuGaO2 hexagonal platelets through Ostwald ripening mechanism, forming high‐density p–n heterojunctions. A parabolic dependence between the size of ZnS microsphere and the growth time is confirmed in this growth. The UV light adsorption of the heterostructure CuGaO2 /ZnS thin film is two times higher than that of the pristine CuGaO2 thin film. Furthermore, the as‐designed "CuGaO2 nanoplate/ZnS microsphere" heterostructure arrays exhibit enhanced photoresponse properties. This work offers a new insight into the rational design of optoelectronic devices from the synergetic effect of p‐type 2D nanoplates as well as n‐type nanostructures such as ZnS, ZnO, CdS, and CdO. Abstract : Large‐area "CuGaO2 nanoplate/ZnS microsphere" p–n heterojunction arrays are successfully grown using a facile low‐temperature solution strategy associated with an oil/water interfacial self‐assembly approach. Such a heterostructured structure shows much higher UV‐light adsorption and superior optoelectronic performance due to the synergetic effects between the CuGaO2 nanoplate and the ZnS microsphere.